A relationship between subclinical hypothyroidism and hematologic parameters in patients with Down Syndrome - Esra Ture; Alaaddin Yorulmaz; Fatih Akin; Ahmet Sert; Abdullah Yazar (SERNEV, 2018)
Introduction: Down syndrome (DS) which is defined astrisomy 21 is the most common chromosomal defect characterized by mentalretardation, hypotonia, dysmorphic facial features, and other distinctivephenotypic characteristics. The prevalence of thyroid disorders in DS is 3% andis significantly higher than in the normal population. In this study we aimed to investigate hematologic parametersof children with DS who had and hadn't subclinical hypothyroidism and comparethem with healthy controls. Methods:This study included 184 patients who were followed upwith genetically diagnosed DS. Completeblood count, levels of serum electrolytes, glucose, urea, liver function tests,thyroid function tests were reviewed. Results: 102 (55.4%)of the patients with DS were male and 82 (44.6%) were female. Mean age was 6.2± 4.0 years. Control group was constituted of outpatienthealthy children. White blood cell count, hemoglobin, hematocrit, andneutrophil counts were found to be significantly lower in patients with DS. Platelet count and plateletcrit levels werefound to be higher and platelet distribution width was lower in patients withDS than in the control group.Conclusion: We found significant differences amonghematological parameters in patients with DS. Subclinicalhypothyroidisminfluences red blood cell distribution width, platelet count and MPV. Knowingthe incidence and severity of hematologic abnormalities in patients with DS willbe beneficial during follow-up in clinical practice.